2015
DOI: 10.1097/rlu.0000000000000904
|View full text |Cite
|
Sign up to set email alerts
|

Glass Microspheres 90Y Selective Internal Radiation Therapy and Chemotherapy as First-Line Treatment of Intrahepatic Cholangiocarcinoma

Abstract: Selective internal radiation therapy combined with concomitant chemotherapy seems a promising strategy as first-line treatment for unresectable intrahepatic cholangiocarcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 19 publications
1
53
1
Order By: Relevance
“…For these patients, palliative treatment, usually in the form of systemic chemotherapy, is the only option of treatment. Selected patients with liver-predominant disease may benefit from liver-directed therapies such as external beam radiation (24, 25) or radioembolization (26, 27). Unfortunately, data suggesting such benefit is based on retrospective series or small phase II trials rather than randomized studies; further data are awaited to confirm the incremental benefit of approaches involving liver radioembolization.…”
Section: Clinical Contextmentioning
confidence: 99%
“…For these patients, palliative treatment, usually in the form of systemic chemotherapy, is the only option of treatment. Selected patients with liver-predominant disease may benefit from liver-directed therapies such as external beam radiation (24, 25) or radioembolization (26, 27). Unfortunately, data suggesting such benefit is based on retrospective series or small phase II trials rather than randomized studies; further data are awaited to confirm the incremental benefit of approaches involving liver radioembolization.…”
Section: Clinical Contextmentioning
confidence: 99%
“…A total of 166 articles were identified using our search criteria for screening (Figure ). Following assessment by the adopted exclusion criteria, 12 studies were identified after thorough assessment of the full manuscripts . Of these, two were excluded because they were subsequently updated and one because it duplicated another more complete report .…”
Section: Resultsmentioning
confidence: 99%
“…Its interest in the palliative treatment of ICC has been demonstrated [7,18,19] and our team recently reported its utility for downstaging huge initially unresectable lesions, thereby enabling secondary resection [8].…”
Section: Discussionmentioning
confidence: 99%
“…Radioembolization with Yttrium-90 (Ytt-90) is a promising method that has already demonstrated its efficacy as a palliative treatment for HCC or ICC, and is an effective therapy for downstaging to resection or LT for HCC [6,7]. Recently, we showed its interest in downstaging huge and unresectable ICCs which enabled secondary resection [8].…”
Section: Introductionmentioning
confidence: 99%